The Existence of Criminal Fines in Law Enforcement of Illegal Fishing Crimes - Rini Fathonah; Mashuril Anwar (Formosa Journal of Multidisciplinary Research, 2023)
Indonesia now deals with the issue of illegal fishing on a regular basis. The Fisheries Law includes fines as one of its penalties for anyone who engage in unlawful fishing. Applying sanctions to those who engage in illicit fishing may boost state income. However, in actuality, the imposition of penalties has brought up fresh issues with implementation. Therefore, the purpose of this research is to read and evaluate the presence of criminal penalties in Indonesian law enforcement as well as the design of criminal fines in the Fisheries Law. This study employs statutory and case-based methodologies in a descriptive manner that is consistent with normative legal research. The study's findings indicate that Articles 84 to 101 of the Fisheries Law are where penalties are defined. The imposition of sanctions for those found guilty of unlawful fishing creates additional issues. Judges continue to often penalize anyone found guilty of unlawful fishing, nevertheless. This requirement puts more strain on prisons and produces accounts receivable for the prosecutor's office, the condition's executor.